SEQUENTIAL INVERSION OF GEOELECTRIC AND GRAVITY METHODS USING PHYSICAL ROCKS PROPERTIES FOR GROUNDWATER STUDY IN TUGUMUKTI, CISARUA, WEST BANDUNG REGENCY - Yuni Azhari, Na'ila
Mapping of saturated and unsaturated water zones is essential due to the importance of water for the survival of living organisms on Earth. Physical properties of rocks, density and resistivity, can be utilized for groundwater modelling studies. This research aims to estimate the boundaries of the saturated water zone (aquifer) and unsaturated water zone in Cisarua, Lembang, by carrying out two geophysical inversion methods, gravity and geoelectric, respectively. The accepted inversion model are the best model which is fulfilled the physical parameter of rocks between minimum and maximum limit value, in both gravity inversion and geoelectric inversion, as well as the conceptual model of the groundwater system. Physical properties of rocks between two limits value as the initial model of both inversion, enabling to shape of the inversion process to generate a model that approaches the conceptual model of groundwater system and geological information of the area. Thereby the mechanism of combining these two inversion geophysical methods can reduce model ambiguity. The inversion results indicate an aquifer average thickness of 20 meters with a density contrast between -0.3 and 0.15 gr/cc and resistivity less than 60 ohm meters. The unsaturated water zone (vadose zone) is found with an average thickness of 5-10 meters at a distance of 0 – 240 m and a thickness of 20 meters at a distance of 250 – 550 m. Vadose zone has density-contrast values ranging from -0.8 to -0.3 gr/cc and resistivity between 60 to 300 ohm meters. Thus, this mechanism can be employed as an initial idea for the development of a joint inversion of two or more methods.